2016
DOI: 10.4314/ahs.v16i2.10
|View full text |Cite
|
Sign up to set email alerts
|

On the way to universal coverage of maternal services in Iringa rural District in Tanzania. Who is yet to be reached?

Abstract: Background: Strategies to tackle maternal mortality in sub-Saharan Africa include expanding coverage of reproductive services. Even where high, more vulnerable women may not access services. No data is available on high coverage determinants. We investigated this in Tanzania in a predicted high utilization area. Methods: Data was collected through a household survey of 464 women with a recent delivery. Primary outcomes were facility delivery and ≥4 ANC visits. Determinants were analysed using multivariate regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
(24 reference statements)
3
17
0
Order By: Relevance
“…In 14 studies, women of high socioeconomic status (SES) attended at least four ANC visits more than those in the lower socioeconomic/wealth strata15 25 27 29 30 32 41 54 64 69 77 89–91 (table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 14 studies, women of high socioeconomic status (SES) attended at least four ANC visits more than those in the lower socioeconomic/wealth strata15 25 27 29 30 32 41 54 64 69 77 89–91 (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Women whose pregnancy was confirmed by missed period rather than urine test were more likely to delay booking ANC visit 87. Women who attended ANC in the first trimester were more likely to attend up to four ANC visits89 (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted by Straneo et al in the Tosamaganga catchment area showed high rates of institutional birth coverage, probably facilitated by the high health facility density 36. However, coverage and quality do not always go together and the poorest women were reported accessing lower-level health services for birth where quality of care is suboptimal due to limited caseloads and poor staffing 37…”
Section: Discussionmentioning
confidence: 99%
“…Mwanza Region had 96.6% ANC coverage, 53.3% health facilities deliveries, 54.2% skilled birth attendances, and 20.7% postpartum check-ups [3]. Other studies in Tanzania showed a 58.3% ANC4+ visits and 87.7% health facility delivery in Iringa rural district [9] and 56% health facilities deliveries in Biharamulo [10].…”
Section: Introductionmentioning
confidence: 99%